Glutamate transporter: an unexpected target for some antibiotics - Mao Jianren (SAGE Publishing, 2005)
Abstract Glutamate transporter (GT) plays a major role in the mechanisms of glutamate homeostasis. Can this transporter system be a therapeutic target for glutamate-mediated neurological disorders? In January's edition of Nature, Rothstein et al (2005) reports that the most commonly used class of antibiotics (β-lactam antibiotics) such as ceftriaxone promoted the expression of GLT1 and demonstrated a functional role in both in vitro and in vivo models of glutamate neurotocixity. These findings indicate that positive promoters of GT expression may have a unique role in neuroprotection through regulating GT expression. This is also encouraging in search for new pharmacological tools for pain management.